A study on cervical lymphadenopathy in a rural based teaching hospital in India - Aparup Dhua; Pranab Mandal; Priya Ranjan Chattopadhyay; Santu Kumar Samanta (Asian Journal of Medical Sciences, 2022)
Background: Presence of cervical lymphadenopathy may indicate serious systemic disease process. Proper evaluation of cervical lymphadenopathy is of extreme clinical importance. Aims and Objective: The study objective was to evaluate clinical and demographic profile of cervical lymphadenopathy, to find the etiology, and to study the role of fine-needle aspiration cytology (FNAC) in it’s etiological diagnosis. Materials and Methods: Prospective observational study was carried out in a rural based teaching hospital in India for 1 year. One hundred and twenty-one patients of more than 12 years of age from both genders were included in the study. Detailed history, clinical, blood examination, radiological, microbiological evaluation, and FNAC from lymph node were done for all patients. Excision biopsy was done for selective cases. Results: It was a male predominant study with male: female ratio of 1.12:1 and mean age of the patient was 34.54 years. Cervical lymphadenopathy was mostly unilateral (77.69%) and it was more common in the right side (43.80%). Tuberculosis (TB) (36.37%) was the most common cause of cervical lymphadenopathy in our study followed by reactive hyperplasia of lymph node (23.14%) and metastatic deposit (19%). Among metastatic deposit, 9 (39.13%) had squamous cell carcinoma, 5 (21.74%) had adenocarcinoma, and 1 (4.35%) had small cell carcinoma. Conclusion: TB is the most common cause of cervical lymphadenopathy followed by reactive hyperplasia and metastatic secondary deposit. FNAC is a simple inexpensive relatively painless rapid and reliable method for diagnosis which can be considered as a frontline investigation and can guide requirement for further investigation in the management of cervical lymphadenopathy.